Takayasu arteritis and ulcerative colitis: coexistence or misdiagnosis? - Azack, A.; Huddam, B.; Koçak, et al., G. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Takayasu arteritis is a chronic inflammatory disease that primarily affects large arteries such as the aorta and its proximal branches.The association between Takayasu arteritis and ulcerative colitis is an extremely rare condition. Ulcerative colitis is an inflammatory bowel disease, clinical presentation is not specific and may mimic Crohn’s disease, radiation colitis, ischemic colitis, a variety of infectious processes, and colitis related to medications. Herein we report a case of Takayasu arteritis who had been misdiagnosed and treated as ulcerative colitis.